Cognitive Behavioral Therapy in School Counseling: Its Role in Student Cognitive Development - Mawarni, Anisa; Taufiq, Agus; Ilfiandra, Ilfiandra; Faizal, Faizal (ANFUSINA: Journal of Psychology, 2024)
The development of optimal cognition is an important factor in student learning and personal development. This study aims to determine the effectiveness of counseling services using a Cognitive Behavior Therapy (CBT) approach in optimizing students' cognitive development. A comprehensive search was conducted using the Taylor & Francis, ScienceDirect, Mendeley, and Google Scholar databases, yielding a total of 70 results. From this number, 20 articles met the exclusion criteria and were deemed feasible, with 13 final studies selected based on the established inclusion criteria. The results of the random effects analysis show a significant positive relationship between the Cognitive Behavior Therapy approach and students’ cognitive development (z = 4.083, p < .001). Keywords: Cognitive Development; Cognitive Behavior Therapy-Based Counseling Services; Study of Literature and Meta-Analysis